Implementation of interleaved converter for fast charging stations - Veerendra, Arigela Satya; Lakshmi, Kambampati; Sekhar, Chavali Punya; Kappagantula, Sivayazi; Kadirgama, Kumaran; Norazlianie, Sazali (Semarak Ilmu Publishing, 2024)
The major goals of this effort are to create an electric vehicle charging station microgrid that combines the utility grid, a solar PV plant, and a bioenergy system as its primary energy sources. Here, the solar system is designed for 15kW, and the energy system is designed for 5kW. To improve the efficiency and maximize the performance of the distributed energy system, a DC-DC converter-based perturb and observe MPPT technique is implemented. The proposed arrangement makes it possible to build a microgrid that is effective, affordable, and distinctively local. The utilization range of electric vehicles is increasing rapidly and still in some areas it is limited due to more charging times. This can be improved by providing fast charging conditions that enable charging a vehicle in less time. To maintain these fast-charging conditions, an efficient, compact-sized DC-DC converter with high power output is required. This paper introduces an interleaved DC-DC power converter to meet the above requirements. The proposed interleaved multi-phase converter, which is part of fast charging stations, can charge the electric vehicle in less than 3 hours. To achieve high power density, ripple reduction on the output current and to improve the efficiency of the converter a space vector modulation technique is applied. The operation of an interleaved converter is analysed theoretically. Simulation analysis of the proposed interleaved power converter shows the good behaviour of the converter and charging conditions of various electric vehicle systems.